Adaptabilidad de tres híbridos de brócoli (Brassica oleracea var Italica) con dos niveles de fertilización química en la parroquia Cañi - Dávila Cajo, Byron Alexander (2025)
Broccoli (Brassica oleracea var. Italica) is currently a non-traditional crop of the Ecuadorian Andes, it is consumed as a fresh product, it is consumed internationally and nationally. Its consumption greatly helps health due to the presence of phenolics and glucosinolates, which have antioxidant activity. The lack of knowledge about broccoli cultivation, ignorance and unwillingness to change their traditional crops are the most common problems in the site, the need to find suitable and profitable crops for the sector to enhance it through the introduction of new cultivars, make them adapt to new forms of cultivation and correct use of chemicals and fertilizers. This research was carried out in the parish of Cañi. The objectives were: (I) to determine the agronomic characteristics of each of the hybrids, (II) to evaluate in which of the fertilization levels the highest productivity was obtained, (III) to determine in which of the treatments the best agronomic and productive characteristics were obtained, (IV) to carry out an economic analysis Benefit/Cost in each treatment. The methodology applied was a randomized complete block design (RCBD) in a factorial arrangement 3x3x3 split plots, the treatments were T1; Sapphire hybrid + 10-30-10, T2; Sapphire hybrid + 15-15-15, T3; Sapphire hybrid + no fertilizer, T4; Avenger hybrid + 10-30-10, T5; Avenger hybrid + 15-15-15, T6; Avenger hybrid + no fertilizer, T7; Maracaibo hybrid + 10-30-10, T8; Maracaibo hybrid + 15-15-15, T9; Maracaibo hybrid + no fertilizer. The agronomic evaluation of the three broccoli hybrids with chemical fertilization was carried out. According to the study carried out, it was determined that the Avenger hybrid obtained the best agronomic and productive characteristics, showing its superiority over the other hybrids, plus the use of 10-30-10 fertilizer with an amount of 6 g per plant at the time of transplanting. A yield of 25250kg/ha was obtained. The benefit-cost ratio of the best treatments that generated a higher income was; T4: Hybrid Avenger + 10-30-10 established a net income of $ 4888.27 and the B/C ratio of 0.94, for each dollar invested there is an income of $ 0.94 dollars.